SUPPORTING THE TRANSITION FROM SCHOOL TO ACTIVE LIFE. CASE STUDY: FEEDBACK ANALYSIS OF THE INTERNSHIPS STUDENTS OF „VASILE ALECSANDRI” UNIVERSITY OF BACAU - MARIA-CRINA RADU; PETRONELA SAVIN; VALENTIN NEDEFF; ROXANA GRIGORE (Journal of Engineering Studies and Research)
At all stages of life, education and training are essential aspects of human development and key factors for economic growth, jobs, and social cohesion. High quality and inclusive training must be a main goal of our society, especially as we live in a very challenging period, governed by the fourth industrial revolution, that transforms economies, jobs, and the society itself. Because of this, the „Vasile Alecsandri” University of Bacau is involved as a partner, with other universities, in a project with European funding, that facilitates practical training of students at economic partners, to increase the employability of graduates and obtain feedback from employers to correlate the curriculum to the labor market. The current paper aims to present a case study related to the feedback offered by the students who carried-out internships at local economic agents, within the above-mentioned project.